Revitalisasi Pasar Sikambing Medan Menjadi Pasar Modern dengan Pendekatan Arsitektur Post Modern - AKbar, Fauzi; rambe, yunita syafitri (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2024)
This article or writing aims to design a modern market in the city of Medan with a Post Modern Architecture approach. Everyone must have a hope in welfare because this is one of the important aspects in people's lives where it greatly influences economic growth in every area such as the city of Medan. The existence of a market is the most important thing in the world of economic business, buying and selling transaction activities will be tangible evidence and also as a benchmark in efforts to increase economic income in an area or region. Based on this, an idea for designing a modern market in the city of Medan arose, the intent and purpose of the design was made to simplify and provide professional comfort to potential customers in the surrounding area.